Comparison between two methods to record occlusal contacts in habitual maximal intercuspation - Cabral, Cláudio Wilson Lima Ferro (2016)
This research evaluated two techniques to record the occlusal contacts in habitual maximal intercuspation obtained in models mounted in semi adjustable articulator and in the mouth using an eight-micrometer carbon paper and sensors (T-Scan II). It was selected a sample of twenty five people, male and female, ages between twenty and twenty five years old with natural dentition. The collected data were visually and statistically evaluated by means of the Spearman coefficient. The results showed that the carbon paper as material used for the occlusal contact records enabled to determine exactly the quantity and its locations in the occlusal surface. However, it did not provide the information on the sequence, time and intensity on how these occur. The T-Scan system enabled to determine the quantity, the sequence and the exact time that they occur, however the system did not determine the exact location of the contacts over the teeth occlusal surface. It was observed that in both methods, the quantity of the occlusal contacts recorded in the mouth was higher than the ones obtained in the articulator and that the sensor thickness did not interfere in the reproduction of the quantity of dental contacts in comparison to the carbon paper.